Public Views on Pulse Oximetry Screening for Critical Congenital Heart Disease. (March 2017) - Kumar, Praveen; Iyengar, Hari; Kumar, Prerna
Objectives: To understand public views on pulse oximetry screening for critical congenital heart disease. Methods: Two hundred thirteen adults read a brief vignette describing the importance of early detection of critical congenital heart disease and then answered five questions on a five-point scale of how likely or unlikely they were to support pulse oximetry screening. Responses were tabulated and analyzed using a Fisher exact test, and logistic regression was used to estimate odds ratios for adjusted associations using generalized estimating equations. Results: Almost 90% of all participants expressed support for routine pulse oximetry screening. The possibility of false positives leading to a delay in discharge, and the potential need for transfer to another facility lowered support but did not reach a statistical significance. The overall support for pulse oximetry screening was strong and consistent between different participant demographics. Conclusion: A large majority of participants in this study support pulse oximetry screening for the early detection of critical congenital heart disease.